Pengaruh Pemberian Pupuk Kandang Kambing dan Pupuk NPK Mashitam Terhadap Pertumbuhan dan Produksi semangka(Citrulus Vulgaris Schard) Varietas Hibrida Baginda F1 - Masyuda Pratama; Yudi Triyanto; Siti Hartati Yusida Saragih (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2020)
The purpose of this study was to determine the effect of the best dose interaction between goat manure and NPK Mashitam on the growth and production of watermelon (Citrulus vulgaris schard) hybrid varieties aginda F1. The implementation of this research was carried out in March-May 2020 in the STIPER Labuhanbatu experimental field. This study used a factorial randomized block design (RBD) consisting of two factors. As the first factor is the dosage treatment of NPK Mashitam fertilizer, which consists of 3 levels, namely N0: without NPK fertilizer treatment N1: NPK Mashitam fertilizer at a dose of 5 gr / plant, and N2: NPK Mashitam fertilizer at a dose of 10 gr / plant, the second treatment factor is Fertilizer. The goat pen consists of 3 levels, namely N0: without treatment. Goat manure, N1: Goat manure at a dose of 500 gr / hole, N2: goat manure at a dose of 1,000 gr / hole. Based on the results of this study it can be concluded that: there was a very real interaction between the treatment of NPK Mashitam fertilizer dosage and the dose of goat manure on plant length variables aged 15, 30, 45 and 60 days, a significant interaction with the variable number of leaves aged 15, 30, 45 and 60 days, the number of leaves aged 15, 30, 45 and 60 days. Leaf width at 15, 30, 45 and 60 days, flowering age and fruit weight. The highest production was produced in the treatment dose of 1000 kg / ha Mashitam organic fertilizer, namely 5.41 kg.  Key words: Effect, Giving goat manure and NPK Mashitam, growth and production of watermelon